A Novel PLP-Dependent Alanine/Serine Racemase From the Hyperthermophilic Archaeon Pyrococcus horikoshii OT-3 - Kawakami, Ryushi; Ohshida, Tatsuya; Sakuraba, Haruhiko; Ohshima, Toshihisa (Frontiers in Microbiology, 2018)
We recently identified and characterized a novel broad substrate specificity amino acid racemase (BAR) from the hyperthermophilic archaeon Pyrococcus horikoshii OT-3. Three genes, PH0782, PH1423, and PH1501, encoding homologs exhibiting about 45% sequence identity with BAR were present in the P. horikoshii genome. In this study, we detected PLP-dependent amino acid racemase activity in the protein encoded by PH0782. The enzyme showed activity toward Ala, Ser, Thr, and Val, but the catalytic efficiency with Thr or Val was much lower than with Ala or Ser. The enzyme was therefore designated Ala/Ser racemase (ASR). Like BAR, ASR was highly stable at high temperatures and over a wide range of pHs, though its hexameric structure differed from the dimeric structure of BAR. No activity was detected in K291A or D234A ASR mutants. This suggests that, as in Ile 2-epimerase from Lactobacillus buchneri JCM1115, these residues are involved in Schiff base formation and substrate interaction, respectively. Unlike BAR, enhanced ASR activity was not detected in P. horikoshii cells cultivated in the presence of D-Ala or D-Ser. This is the first description of a PLP-dependent fold type I Ala/Ser racemase in archaea.